Assessing and managing the ecological impacts of paved roads (National Academies Press, 2005)
All phases of road development from construction and use by vehicles to maintenance affect physical and chemical soil conditions, water flow, and air and water quality, as well as plants and animals. Roads and traffic can alter wildlife habitat, cause vehicle-related mortality, impede animal migration, and disperse nonnative pest species of plants and animals. Integrating environmental considerations into all phases of transportation is an important, evolving process. The increasing awareness of environmental issues has made road development more complex and controversial. Over the past two decades, the Federal Highway Administration and state transportation agencies have increasingly recognized the importance of the effects of transportation on the natural environment. This report provides guidance on ways to reconcile the different goals of road development and environmental conservation. It identifies the ecological effects of roads that can be evaluated in the planning, design, construction, and maintenance of roads and offers several recommendations to help better understand and manage ecological impacts of paved roads.